2022
DOI: 10.1017/cts.2022.418
|View full text |Cite
|
Sign up to set email alerts
|

Treatment completion among justice-involved youth engaged in behavioral health treatment studies in the United States: A systematic review and meta-analysis

Abstract: Justice-involved youth (JIY) have high rates of behavioral health disorders, but few can access, much less complete, treatment in the community. Behavioral health treatment completion among JIY is poorly understood, even within treatment studies. Measurement, reporting, and rates of treatment completion vary across studies. This systematic review and meta-analysis synthesizes the literature on rates of treatment completion among JIY enrolled in research studies and identifies potential moderators. After system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Third, the abrupt and intensive participation in individual therapy required in most residential placements can be extremely triggering for youth who have experienced complex or developmental trauma and, thus, struggle with attachment, trust, and vulnerability with others. In fact, research has demonstrated that individual therapy can be effective for youth with significant relational poverty (few meaningful connections to other people), but may have minimal or even negative impact for youth who already have a consistent, supportive, and relationally-enriched community ( Renick, 2018 ; Johnson-Kwochka et al, 2022 ). Finally, high levels of turnover, absenteeism, and burnout among residential placement staff are directly related to increased juvenile risk, recidivism, and treatment failure ( Wolff et al, 2022 ), likely because such staffing difficulties result in abrupt transfers of care and a chaotic and unpredictable “therapeutic web” or “social milieu”– the opposite of what trauma-exposed youth need ( Ludy-Dobson and Perry, 2010 ).…”
Section: Policy Considerations and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the abrupt and intensive participation in individual therapy required in most residential placements can be extremely triggering for youth who have experienced complex or developmental trauma and, thus, struggle with attachment, trust, and vulnerability with others. In fact, research has demonstrated that individual therapy can be effective for youth with significant relational poverty (few meaningful connections to other people), but may have minimal or even negative impact for youth who already have a consistent, supportive, and relationally-enriched community ( Renick, 2018 ; Johnson-Kwochka et al, 2022 ). Finally, high levels of turnover, absenteeism, and burnout among residential placement staff are directly related to increased juvenile risk, recidivism, and treatment failure ( Wolff et al, 2022 ), likely because such staffing difficulties result in abrupt transfers of care and a chaotic and unpredictable “therapeutic web” or “social milieu”– the opposite of what trauma-exposed youth need ( Ludy-Dobson and Perry, 2010 ).…”
Section: Policy Considerations and Implicationsmentioning
confidence: 99%
“…We undervalue the powerful therapeutic impact of a caring teacher, coach, neighbor, grandparent, and a host of other potential ‘co-therapists,’ ( Ludy-Dobson and Perry, 2010 , p. 39). Research has demonstrated the benefits of group and family intervention modalities over individual therapy structures for justice-involved youth with relationally-enriched environments ( Johnson-Kwochka et al, 2022 ). Accordingly, if the trauma-exposed youth has a strong and consistent therapeutic web, consider how you can leverage and strengthen those existing relationships within the probation or intervention plan, rather than creating a structure that disrupts meaningful and safe connections in the youth’s home and community.…”
Section: Actionable Recommendationsmentioning
confidence: 99%